2022
DOI: 10.1016/j.jtho.2021.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Deep RNA Sequencing Revealed Fusion Junctional Heterogeneity May Predict Crizotinib Treatment Efficacy in ALK-Rearranged NSCLC

Abstract: Introduction: Gene fusion variants in ALK-rearranged NSCLC may predict patient outcomes, but previous results have been inconclusive. Fusion isoforms coexisting in the same tumor may affect the efficacy of targeted therapy, but they have not been investigated.Methods: Patients with ALK-rearranged NSCLC who received crizotinib treatments were recruited. Precrizotinib tumor tissues were analyzed by the anchored multiplex polymerase chain reaction for targeted RNA sequencing. Kaplan-Meier and Cox regression were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Further comparative analysis of the transcripts and the amino acid sequences showed that partial retention of exon 20 could ensure the in‐frame sequence with integrity of the ALK kinase domain [ 43 , 44 ]. Patients harbouring multiple EML4‐ALK variants implied a poor prognosis due to the high heterogeneity in the tumour tissue [ 45 ]. Therefore, RNA‐based NGS showed an advantage in detecting fusion patterns in which multiple variants coexist, and more precise splicing results at the transcription level were illustrated.…”
Section: Discussionmentioning
confidence: 99%
“…Further comparative analysis of the transcripts and the amino acid sequences showed that partial retention of exon 20 could ensure the in‐frame sequence with integrity of the ALK kinase domain [ 43 , 44 ]. Patients harbouring multiple EML4‐ALK variants implied a poor prognosis due to the high heterogeneity in the tumour tissue [ 45 ]. Therefore, RNA‐based NGS showed an advantage in detecting fusion patterns in which multiple variants coexist, and more precise splicing results at the transcription level were illustrated.…”
Section: Discussionmentioning
confidence: 99%
“… 252 Similarly, RNA sequencing revealed that ALK junctional heterogeneity in NSCLC may predict resistance to crizotinib. 253 Likewise scRNA-seq of chemoresistant cervical cancer revealed induction of the (PI3K)/AKT pathway. 254 Thus, it is possible to infer the mechanisms of acquired resistance and to monitor clonal changes of tumors in response to therapy.…”
Section: Experimental Methods For Identification Of Fusion Oncogenesmentioning
confidence: 99%
“…Approximately 50–60% of patients with ALK kinase-domain mutations are resistant to second-generation ALK TKIs [ 49 ]. It may be important to note that ALK fusion variants may play a role in the development of ALK inhibitor resistance on-target [ 50 ]. Several recurrent acquired mutations in ALK confer resistance by decreasing drug binding, including I1171T/N/S, V1180L, G1269A and G1202R [ 51 ].…”
Section: Molecular Targetsmentioning
confidence: 99%